Diffusion-weighted magnetic resonance imaging for diagnosis of post-operative paediatric cholesteatoma. Issue 5 (3rd May 2023) - McCallum, R; Coleman, H; Pervaiz, H; Irwin, G; McAllister, K
Abstract: Objectives: High rates of recidivism are reported after paediatric cholesteatoma surgery. Our practice has adapted to include non-echoplanar diffusion-weighted magnetic resonance imaging for the diagnosis of residual or recurrent cholesteatoma. This audit aimed to evaluate the performance of non-echoplanar diffusion-weighted magnetic resonance imaging in our paediatric population. Methods: A retrospective review was conducted of non-echoplanar diffusion-weighted magnetic resonance imaging scans performed to detect residual disease or recurrence after surgery for cholesteatoma in children from 1 January 2012 to 30 November 2017 in our centre. Follow-up diffusion-weighted magnetic resonance imaging scans were reviewed to 16 August 2019. Results: Thirty-four diffusion-weighted magnetic resonance imaging scans were included. The sensitivity and specificity values of diffusion-weighted magnetic resonance imaging for detecting post-operative cholesteatoma were 81 per cent and 72 per cent, respectively. Positive predictive and negative predictive values were 72 per cent and 81 per cent, respectively. Conclusion: Use of diffusion-weighted magnetic resonance imaging is recommended as a replacement for routine second-look surgical procedures in the paediatric population. However, we would caution that patients require close follow up after negative diffusion-weighted magnetic resonance imaging findings.